Nursing care a patient with duodenal fistula and deep venous thrombosis after resection of giant retroperitoneal tumor (1例腹膜后巨大肿瘤切除术后合并十二指肠瘘及深静脉血栓患者的护理) - WANG Wei (汪维); QU Xiaoling (屈晓玲); YANG Ting (杨婷) (中西医结合护理)
This paper summarized the nursing experience a patient with duodenal fistula and deep venous thrombosis (DVT) after resection of giant retroperitoneal tumor. Nursing interventions included preoperative evaluation, DVT-associated nursing, skin care, enteral nutrition, etc. Diversified interventions before and after surgery are required to prevent the postoperative complicanions and improve the recovery. (本文总结1例全麻下行腹膜后巨大肿瘤切除术后合并十二指肠瘘及深静脉血栓的护理经验, 包括术前评估、深静脉血栓护理、皮肤管理、肠内营养护理等, 通过多元化的术前、术后护理, 积极预防并发症, 提高患者舒适度, 促进患者早日康复。)